Examining Health Professional Trainee Burnout: Lessons Learned Using Qualitative Inquiry to Elicit Rich Data - Ahlness, Ellen A.; Levy, Deborah R. (Applied Clinical Informatics, 2025)
Health professionals (HPs) trainee burnout is hard to capture. A lack of rigorous review and systematic methodological consideration hinders the development of qualitative methodological tools that can elicit rich and trustworthy qualitative data on HPs trainee burnout.This study aimed to report the process, results, and lessons learned while developing and pilot testing a qualitative tool to assess HPs' trainee experiences of burnout to complement quantitative tools.We developed a set of semistructured interview questions (n = 3) probing into HP trainee burnout and refined them through a Modified Delphi process. We, then, planned pilot testing of the qualitative tool in initial interviews with HP trainees.We developed a three-question set of semistructured interview questions to probe burnout for HP trainees, which were refined using a Modified Delphi approach (n = 10 subject matter experts). We conducted pilot testing (n = 43 interviews with n = 14 trainees). We developed a novel qualitative tool to assess HPs trainee experiences of burnout, consisting of three core questions and three follow-up probes that elicit data on key dimensions of HPs trainee burnout for integration into a structured or semistructured interview guide.We present results as lessons learned, which can support the further development of tools to articulate HPs' trainee perspectives in studying burnout, especially during health system transitions. Developing qualitative measurement tools designed to be used with well-validated, established quantitative tools may be a complex process, but it is critical in efforts to mitigate HP trainee burnout.
Keywords: qualitative methodology; interviews; burnout; health professional trainees